The Influence of Class Management on the Learning Activities of Class V Students at SDN Jatibaru II - Khoerunisa; Hinggil Permana; Ceceng Syarif Husein (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to determine the effect of classroo m manajement on the active learning of class V students at SDN Jatibaru II. This type of research uses quantitative methods using a correlational approach. The population in this study was students at SDN Jatibaru II with a total of 242 students and the sample used was 47 respondents. The measuring instruments used are instruments for collecting quantitative or statistical data. The data analysis techniques used are descriptive statistical data analysis and inferential statistical analysis. Based on data analysis techniques, class management is in the medium category and students’ active learning is in the medium category. It is said that class management has a positive learning of class V students at SDN Jatibaru II.